(untitled) (Research, Society and Development, 2020)
Cyniclomyces guttulatus is a commensal fungus of the digestive tract of rabbits and rodents, but it has also been diagnosed in dogs, being responsible for diarrhea, and it may also be present in healthy dogs. The aim of this study was to detect the presence of this agent in dog feces and also to observe if there was association with other parasites. To perform this work, 150 environmental fecal samples were collected, present on the shores of Pelotas, RS. The techniques used for processing the material were Faust (1938), Willis-Molay (1921) and Hoffman, Pons and Janer (1934). Among the samples tested, 15 were positive for C. guttulatus (10%), 4 with contamination by this agent alone and 11 with association with other parasites, representing 26.7% and 73.3% respectively. From the results found, it is concluded that C. gutulattus is often found in animals affected by another genus of parasite, showing its opportunistic character, however it can also be found in healthy animals.